2005
DOI: 10.1590/s1415-43662005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Análise de métodos de estimativa de evapotranspiração na otimização de sistemas de drenagem

Abstract: Inúmeros são os métodos para se estimar a evapotranspiração potencial (ETP) em que os mais simplificados apresentam limitações quanto à precisão dos resultados obtidos e os mais complexos apontam a dificuldade de se dispor de todos os dados necessários ao cálculo. No presente trabalho, compararam-se os métodos de Thornthwaite e Camargo com o de Penman-Monteith, tomado como padrão, com o objetivo de se verificar qual a influência da utilização de cada método na estimativa da ETP diária sobre o dimensionamento e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Within this context, the SISDRENA model simulates the performance of one-dimensional drainage systems (Miranda et al, 1998). Other researchers have used this model for different scientific questions (Silva et al, 2005;Duarte et al, 2002;Mingoti et al, 2006). However, there is a lack of research on using this model to simulate future scenarios of climate change.…”
mentioning
confidence: 99%
“…Within this context, the SISDRENA model simulates the performance of one-dimensional drainage systems (Miranda et al, 1998). Other researchers have used this model for different scientific questions (Silva et al, 2005;Duarte et al, 2002;Mingoti et al, 2006). However, there is a lack of research on using this model to simulate future scenarios of climate change.…”
mentioning
confidence: 99%
“…Silva (2011) for the Pernambuco region indicated that the Priestley-Taylor method presented one of the best performances for estimating ETo. Silva et al (2005) working with the methods of Thornthwaite and Camargo and comparing them with that of Penman-Monteith found that these underestimated those obtained by the method of Penman-Monteith. Thus, ET can also be estimated using the method proposed by Penman-Monteith with the parameterization proposed by FAO (ALLEN et al, 1998).…”
Section: Evapotranspiration Estimation Methodsmentioning
confidence: 96%
“…According to Silva et al (2006), lysimeters can have different configurations depending on the climate, availability of materials and costs involved in their construction. Studies carried out with lysimeters installed in the field have shown to be a sustainable tool for determining the components of the water balance for the Soil-Plant-Atmosphere System (SSPA) (LOOS et al, 2007).…”
Section: Evapotranspiration Measurement Methodsmentioning
confidence: 99%
“…Sentelhas et al (2008) aplicaram o método PM-FAO no desenvolvimento do balanço hídrico climatológico de Thornthwaite & Mather (1955), para todo o Brasil, considerando o PM-FAO o mais representativo para a estimativa da demanda de evapotranspiração (ETp). O mesmo procedimento foi utilizado por Carvalho et al (2008) Para dimensionamento econômico de um sistema de drenagem, na região de Piracicaba, SP (Silva et al 2005a), embora as estimativas por TW e CAM subestimassem a ETo, em relação à PM-FAO, os autores concluíram que não houve influência dos métodos selecionados, no dimensionamento. Barreto (2006) e Medeiros (2008), em duas localidades do Estado de São Paulo (Brotas e Jaboticabal, respectivamente), em estudos semelhantes, comparando métodos alternativos para a ETo com PM-FAO, verificaram bons desempenhos atribuídos ao método TW.…”
Section: Desempenho Dos Métodos De Estimativa Da Etounclassified